The inflammasomes - Couillin, Isabelle; Pétrilli, Virginie; Martinon, Fabio; SpringerLink (Online service). (Basel Springer, 2011)
The inflammasome was first described in 2002 as a molecular complex activating proinflammatory caspases and therefore regulating the maturation and biological activities of cytokines such as IL-1 and IL-18. This finding was substantiated by the identification of several mutations in the cias1 gene, encoding the human NLRP3 protein, responsible for several autoinflammatory disorders such as the Muckle Wells syndrome. Since, the interest for this complex has constantly increased and several inflammasome complexes with different specificities have been described. These inflammasomes sense a wide variety of pathogens and danger signals and are key players in the inflammatory response. With the contributions of leading international experts in the field, this book provides an extensive overview of the current knowledge of inflammasome biology and their role in health and disease.
Molecular definition of inflammasomes -- Pyroptosis: A Caspase-1-dependent programmed cell death and a barrier to infection -- Activation of the inflammasome by bacterial pathogens -- The Role of Inflammasomes in Viral Infection -- Inflammasome activation in response to eukaryotic pathogens -- Inflammasome activation by pathogenic crystals and particles -- Inflammasome activation by danger signals -- Toll like receptors and inflammasomes -- Inflammasome in the skin -- Cancer, inflammasomes and adjuvanticity -- Inflammasome and lung pathologies -- Mechanisms of NLRP3 inflammasome activation in CAPS patients -- Activation and regulation of the NLRP3 inflammasome -- Treatment of inflammasome-related disorders.
Electronic reproduction.
Keywords: Inflammation -- Pathophysiology; Inflammation -- Immunological aspects; Inflammation -- Molecular aspects; Inflammation -- Mediators; Inflammasomes; Electronic books